Metodología estadística: bases para el establecimiento de políticas adecuadas para el manejo del arbolado urbano en la Ciudad de México - Aldama, Alejandro (2003)
An Exploratory analysis using arboricultural and ecological statistical approaches of a representative sample of Mexico City’s street trees were followed by a confirmatory study through Path Analysis to test hypothesis stating causal relationships among different variables. All this in order to evaluate and to manage the quality of Mexico City’s Urban Forest.